Decoding the chemotactic signal. Issue 2 (6th June 2018) - Thomas, Monica A.; Kleist, Andrew B.; Volkman, Brian F.
Abstract: From an individual bacterium to the cells that compose the human immune system, cellular chemotaxis plays a fundamental role in allowing cells to navigate, interpret, and respond to their environments. While many features of cellular chemotaxis are shared among systems as diverse as bacteria and human immune cells, the machinery that guides the migration of these model organisms varies widely. In this article, we review current literature on the diversity of chemoattractant ligands, the cell surface receptors that detect and process chemotactic gradients, and the link between signal recognition and the regulation of cellular machinery that allow for efficient directed cellular movement. These facets of cellular chemotaxis are compared among E. coli, Dictyostelium discoideum, and mammalian neutrophils to derive organizational principles by which diverse cell systems sense and respond to chemotactic gradients to initiate cellular migration. Abstract : We review the signal recognition process in mammalian neutrophils in order to derive general principles by which diverse cell systems sense and respond to chemotactic gradients to initiate cellular migration.